REFORMASI BIROKRASI SUATU USAHA UNTUK MENINGKATKAN KUALITAS PELAYANAN PUBLIK - Namlis, Achmad (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2015)
The creation of bureaucratic rule through political process impacts the often conflicting interests. The difficulty of implementing change is probably because political consensus is not easily obtained. Regulations are often made in greater details expecting to regulate the behavior of organizations and bureaucracy. However, most regulations clash one another, so regulations are changed before it was even implemented, and the change is also in conflict with others. Changes are often difficult because the changing demand is not only for the rules, but also the bureaucracy that is closely related to mental attitude or the man behind the system. If the public bureaucracy in the public service is not qualified, bureaucracy will be abandoned by users (citizens), and it means it has failed the mission of providing services to the public. This is what happens in the Indonesia’s transition government entering the reformation era, therefore legislations need to be created in greater detail to regulate the behavior of organizations and government bureaucracy.Keywords: reformation, bureaucracy, public service